Fichte and the phenomenological tradition - Waibel, Violetta L.; Breazeale, Daniel; Rockmore, Tom, 1942- (De Gruyter, 2010)
This volume is a collection of previously unpublished papers dealing with the neglected "phenomenological" dimension of the philosophy of Johann Gottlieb Fichte, which it compares and contrasts to the phenomenology of his contemporary Georg Wilhelm Friedrich Hegel and to that of Edmund Husserl and his 20th century followers. Issues discussed include: phenomenological method, self-consciousness, intersubjectivity, temporality, intentionality, mind and body, and the drives. In addition to Fichte, authors discussed include: Hegel, Brentano, Husserl, Heidegger, Sartre, Levinas, and Ricœur